The Influence of Entrepreneurial Literacy, Modernity, and Government Support on Community Welfare through Community Empowerment as a Mediating Variable - Syamsu Rijal; Nur Irmayanti Mulyani; Andi Tenri Ampa; Nurjannah (International Journal of Technology and Education Research, 2025)
Through community empowerment, this study seeks to examine how entrepreneurial literacy, modernity, and government support affect community welfare. A t of 132 culinary MSME actors in Takalar Regency, South Sulawesi Province, were selected as the research sample. A questionnaire was used to collect data, and structural equation modeling (SEM) was employed for analysis. The findings indicate that community empowerment is positively and significantly influenced by entrepreneurial literacy, modernity, and government support. Furthermore, it was shown that community empowerment significantly enhances community welfare. In addition, the study reveals that the relationship between entrepreneurial literacy, modernity, and government support and community welfare is mediated by community empowerment.